L’efficacité de la politique budgétaire et de la politique monétaire dans la gestion macroéconomique des petites économies insulaires en développement : application au cas de Sainte-Lucie - Louis Dupont (Études Caribéennes)
The effectiveness of monetary and fiscal policy has been the centre of debate between keynesians and the monetarists for a long time. However, the results of numerous empirical studies are inconclusive, suggesting that none of the policies can be thought of as superior to the other and their relative effectiveness in any economy depends on the prevailing economic, social and political conditions at any point in time. In spite of this controversy and dilemma, we try to verify in the case of small island developing states, especially Saint Lucia if the results were contrasted, then what would be economic implications in this country. In this context, in order to determine the influence of fiscal and monetary policy on the economic activity in Saint Lucia, we employed a VEC model on the series of yearly data for the period 1995-2023. The results obtained show that monetary policy is more effective in stimulating economic growth compared to fiscal policy. Also, the empirical results point out that the optimal size of government from Armey curve is estimated at 24.4% against a staff level of 22.2%. They show that the state spends below its potential growth. Hence, the overall conclusion is that government should pay more attention to the fiscal policy to improve its efficiency in the future.Finally, in order to improve the macroeconomic effectiveness of these policies, a “policy-mix” is also estimated for stimulating economic growth in this country. This coordination has positive effects on the economic performance of Saint Lucia.